Three-dimensional imaging in periodontal diagnosis – Utilization of cone beam computed tomography - Mohan, Ranjana (Medknow Publications, 2011)
In the field of periodontology and implantology, assessment of the condition of teeth and surrounding alveolar bone depends largely on two-dimensional imaging modalities such as conventional and digital radiography. Though these modalities are very useful and have less radiation exposure, they still cannot determine a three-dimensional (3D) architecture of osseous defects. Hence, an imaging modality which would give an undistorted 3D vision of a tooth and surrounding structures is essential to improve the diagnostic potential. Cone-beam computed tomography (CBCT) provides 3D images that facilitate the transition of dental imaging from initial diagnosis to image guidance throughout the treatment phase. This technology offers increased precision, lower doses, and lower costs when compared with medical fan-beam CT. This review discusses all the finer details of CBCT which not only reveals 3D architecture of the periodontium but also helps to reconstruct it.